Management of Forearm Fracture in Adolescence - Tania F; Siswanto BA; Rusdianto IA; Pramantha B (Cermin Dunia Kedokteran, 2021)
Forearm shaft fracture usually occurs because of indirect trauma, mainly when a child protects themself by an outstretched upper extremity during a fall. CRIF with TENS can be the treatment of choice in adolescents with simple forearm fractures, especially returning to pre-injury function and physical appearance. The patient had a history of fractures of both bones of the right forearm three months before, and the fractures were fixated using TENS. The satisfying outcomes (faster return to his initial ability to play sport, without any dysfunction, visible no big scar) were why we recommended using TENS to fixate the current fractures. Fraktur tulang lengan bawah biasanya terjadi akibat trauma tak langsung, umumnya jika seseorang berusaha menahan tubuhnya saat terjatuh. Teknik CRIF dengan TENS merupakan salah satu yang terpilih untuk tata laksana fraktur lengan bawah sederhana. Pasien memiliki riwayat fraktur kedua tulang lengan kanan 3 bulan sebelumnya dan fraktur difiksasi menggunakan TENS, hasilnya memuaskan (lebih cepat kembali ke kemampuan awal untuk berolahraga, tanpa disfungsi, tidak terlihat bekas luka besar) merupakan alasan kami merekomendasikan penggunaan TENS untuk memfiksasi fraktur saat ini.